In-situ curing additive, curable electrolyte containing in-situ curing additive and high-safety semi-solid secondary battery

By using -C = C, -COO-and -SI-O group in situ solidification monomer I and II, cross-linking and complex form a stable electrolyte structure, solving the oxidation of traditional solid batteries at high voltage conditions under high voltage conditions The problem of restoring the reaction realizes the battery with high chemical performance and high safety performance.

CN119381561AActive Publication Date: 2025-01-28TIANMU LAKE INST OF ADVANCED ENERGY STORAGE TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411519281.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-01-28
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

Traditional solid-state batteries are prone to redox reactions under high voltage conditions, resulting in the generation of by-products, increase in battery impedance, decrease in circulation performance, and may cause expansion or explosion.

Method used

Adopt the original curing monomer I and II of -c = C, -Coo-and -SI-O groups at the same time. Through cross-linking and complexation, cross-linking points, improving electrochemical performance, and reducing oxidation The reaction occurs.

Benefits of technology

The combination of high -power chemical properties and high safety performance has been achieved, the internal impedance of the battery is reduced, the occurrence of side -by -side reactions is reduced, and the cycle stability and safety of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381561A_ABST
    Figure CN119381561A_ABST
Patent Text Reader

Abstract

The invention discloses an in-situ curing additive containing in-situ curing monomers I and II, a curable electrolyte containing the in-situ curing additive, and a high-safety semi-solid secondary battery for constructing a semi-solid electrolyte by using the curable electrolyte, the in-situ curing monomer I has a structure as shown in a formula 1: # imgabs 0 #, and the in-situ curing monomer II has a structure as shown in a formula 2: # imgabs 1 #, r < 1 > to R < 3 > are selected from C1-C4 alkyl groups, alkoxy groups, halogenated alkyl groups or halogenated alkoxy groups, R < 4 > is selected from C1-C6 alkylene groups or halogenated alkyl groups, R < 5 > is selected from C1-C2 alkyl groups or halogenated alkyl groups, R < 6 > is selected from C1-C4 alkylene groups or halogenated alkyl groups, and R < 6 > is selected from C1-C4 alkylene groups or halogenated alkyl groups; according to the invention, the in-situ curing monomer I is introduced into the curable electrolyte, so that crosslinking of the curable electrolyte is realized, and the safety and stability of the battery are improved; by compounding the in-situ curing monomer I and the in-situ curing monomer II, the electrochemical performance of the battery is improved, the redox reaction is reduced, and the curable electrolyte with high electrochemical capacity and high safety and the safe semi-solid secondary battery are obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to an in-situ curing additive, a curable electrolyte containing the in-situ curing additive, and a highly safe semi-solid secondary battery. Background Art

[0002] Solid-state batteries have shown significant advantages in improving battery safety performance. Traditional solid-state batteries usually prepare solid electrolytes by in-situ curing monomers. However, although solid-state batteries prepared by in-situ curing monomers as electrolytes show good performance under some conditions, their own redox stability and electrochemical efficiency are often not taken into account. For example, polyethylene oxide (PEO) has good ionic conductivity, but it is easily oxidized under high voltage conditions, so it cannot work normally in a voltage system exceeding 4.2V; and polyacrylonitrile (PAN) performs well in high voltage resistance, but its ionic conductivity is low, which will affect the overall performance and efficiency of the battery when used to prepare solid-state batteries.

[0003] For in-situ curing monomers, anti-oxidation and anti-reduction properties are very important. When the in-situ curing monomers form a solid electrolyte, the occurrence of redox reactions may not only lead to the production of by-products that increase battery impedance and reduce cycle performance, but may also produce gases that cause the solid electrolyte or battery structure to expand and change or even explode. Therefore, redox reactions should be avoided as much as possible in the solid electrolyte constructed by in-situ curing monomers. However, it is not easy to simultaneously improve the electrochemical properties and anti-oxidation and anti-reduction properties of in-situ curing monomers. Traditional methods of avoiding redox reactions (such as introducing antioxidants) may require sacrificing the ionic conductivity of the electrolyte, while methods of improving conductivity may reduce anti-oxidation and anti-reduction capabilities.

[0004] Therefore, how to maintain the excellent electrochemical properties of in-situ cured monomers while improving their anti-oxidation and anti-reduction capabilities has become a challenge. Summary of the invention

[0005] In view of the problems existing in the prior art, the present invention firstly utilizes an in-situ curing monomer I containing -C=C, -COO- and -Si-O groups to realize the crosslinking of a curable electrolyte, optimizes the crosslinking sites, and improves the electrochemical performance of the curable electrolyte; then utilizes the compounding effect of the in-situ curing monomer I and the in-situ curing monomer II to further improve the ion conductivity of the curable electrolyte, optimize the three-dimensional crosslinking structure, reduce the occurrence of redox reactions, and greatly improve the battery safety performance while achieving high electrochemical capacity.

[0006] The present invention provides an in-situ curing additive, comprising an in-situ curing monomer I and an in-situ curing monomer II. The in-situ curing monomer I has a structural formula of:

[0007]

[0008] Wherein, R1-R3 are selected from C1-C4 alkyl, alkoxy, haloalkyl or haloalkoxy, R4 is selected from C1-C6 alkyl or haloalkyl, and R5 is selected from C1-C2 alkyl or haloalkyl;

[0009] The structural formula of the in-situ curing monomer II is

[0010]

[0011] Wherein, R6 is selected from C1-C4 alkyl or halogenated alkyl.

[0012] The present invention also provides a curable electrolyte, comprising an in-situ curing additive dispersed in a solvent.

[0013] The present invention also provides a highly safe semi-solid secondary battery, comprising a semi-solid electrolyte constructed of in-situ curing monomers dispersed in a curable electrolyte.

[0014] As some exemplary preferred schemes, in the structural formula of the in-situ curing monomer I, the number of alkoxy groups in R1-R3 is less than 3, R1-R3 are selected from C1-C2 alkyl, alkoxy, haloalkyl or haloalkoxy, R4 is selected from C1-C3 alkylene or halogenated hydrocarbon, R5 is selected from C1-C2 alkyl or haloalkyl, and in the structural formula of the in-situ curing monomer II, R6 is selected from C1-C2 alkylene or halogenated hydrocarbon.

[0015] As a further solution, the present invention also provides an in-situ curing monomer I selected from One of the in-situ curing monomers II is selected from allyl-2-cyanoacrylate.

[0016] As a further solution, the ratio of the in-situ curing monomer I to the in-situ curing monomer II is selected from a range of 2:1 to 20:1.

[0017] As a further solution, the ratio of the in-situ curing monomer I to the in-situ curing monomer II is selected from a range of 4:1 to 10:1.

[0018] As a further solution, the total mass content of the in-situ curing monomer I and the in-situ curing monomer II in the curable electrolyte is 0.2% to 7.5%.

[0019] As a further solution, the total content of the in-situ curing monomer I and the in-situ curing monomer II in the curable electrolyte is 0.5% to 5%.

[0020] As a further solution, the curable electrolyte further includes a solvent, an additive, an inorganic electrolyte salt and an initiator.

[0021] As a further embodiment, the solvent is selected from one or more of carbonate compounds, carboxylate compounds, fluorinated compounds, ethers and epoxy compounds.

[0022] As a further embodiment, the carbonate compound is selected from any one or more of cyclic carbonate compounds and chain carbonate compounds.

[0023] As a further solution, in the curable electrolyte of the present invention, the additive is selected from at least one of lithium salt compounds, nitrile compounds, organosilicon compounds, sultone compounds, and sulfate compounds.

[0024] As a further solution, in the curable electrolyte of the present invention, the inorganic electrolyte salt is selected from at least one of borates, phosphates, sulfates, nitrates, antimonates, arsenates and chlorates.

[0025] As a further embodiment, the inorganic electrolyte salt is substituted with fluorine.

[0026] As a further embodiment, the inorganic electrolyte salt is selected from LiPF6.

[0027] As a further embodiment, the initiator is selected from one or more of ammonium persulfate, sodium persulfate, potassium persulfate, hydrogen peroxide, tert-butyl peroxide, dibenzoyl peroxide, and azobisisobutyronitrile.

[0028] The high-safety semi-solid secondary battery further includes a positive electrode sheet, a negative electrode sheet and a separator.

[0029] As a further solution, the positive electrode sheet includes a positive electrode active material, a positive electrode binder, a positive electrode conductor, and a positive electrode current collector.

[0030] As a further solution, the positive electrode active material is selected from at least one of transition metal composite oxides and transition metal phosphate compounds.

[0031] As a further embodiment, the transition metal composite oxide has a general chemical formula selected from (A) x M1 1-p B1 p O2、r(A)2Mn 1-q B2 q O3·(1-r)AM2 1-s B3 s B3O2, (A) y (M3 2-h B4 h)Any one of O4, 0.05 ≤ x, 0 ≤ p ≤ 0.4, 0 ≤ q ≤ 0.4, 0 ≤ s ≤ 0.4, 0 ≤ r ≤ 1, y ≤ 1.2, 0 ≤ h ≤ 0.8, where A is a de-embeddable active metal ion, specifically including Li+, Na+, K+, Mg2+, Ca 2 + any one or more of them, M1, M2 、 M3 is one or more transition metal elements, specifically including scandium (Sc), yttrium (Y), lanthanide elements (from lanthanum (La) to lutetium (Lu)), titanium (Ti), zirconium (Zr), hafnium (Hf), vanadium (V), niobium (Nb), tantalum (Ta), chromium (Cr), molybdenum (Mo), tungsten (W), manganese (Mn), technetium (Tc), rhenium (Re), iron (Fe), ruthenium (Ru), osmium (Os), cobalt (Co), rhodium (Rh), iridium (Ir), nickel (Ni), palladium (Pd), platinum (Pt), copper (Cu), silver (Ag), gold (Au), zinc (Zn), cadmium (Cd), mercury (Hg) one or more of them, B1, B2, B3, B4 are doping elements, specifically including aluminum (Al), cobalt (Co), magnesium (Mg), tantalum (Ta), tungsten (W), niobium (Nb), zirconium (Zr), calcium (Ca), vanadium (V), molybdenum (Mo), chromium (Cr), lanthanum (La), scandium (Sc), lutetium (Lu), yttrium (Y) and boron (B) one or more of them.

[0032] As a further solution, the chemical general formula of the transition metal phosphate compound is (C) z (M4 1-v B5 v )PO4, 0 < z ≤ 1, 0 ≤ v ≤ 0.4, C represents a de-embeddable active metal ion, specifically including Li+, Na+, K+, Mg2+, Ca 2 + any one or more of them, M4 represents one or more transition metal elements, specifically including scandium (Sc), yttrium (Y), lanthanide elements (from lanthanum (La) to lutetium (Lu)), titanium (Ti), zirconium (Zr), hafnium (Hf), vanadium (V), niobium (Nb), tantalum (Ta), chromium (Cr), molybdenum (Mo), tungsten (W), manganese (Mn), technetium (Tc), rhenium (Re), iron (Fe), ruthenium (Ru), osmium (Os), cobalt (Co), rhodium (Rh), iridium (Ir), nickel (Ni), palladium (Pd), platinum (Pt), copper (Cu), silver (Ag), gold (Au), zinc (Zn), cadmium (Cd), mercury (Hg) one or more of them, B5 is a doping element, specifically including aluminum (Al), cobalt (Co), magnesium (Mg), tantalum (Ta), tungsten (W), niobium (Nb), zirconium (Zr), calcium (Ca), vanadium (V), molybdenum (Mo), chromium (Cr), lanthanum (La), scandium (Sc), lutetium (Lu), yttrium (Y) and boron (B) one or more of them.

[0033] As a further embodiment, the positive electrode binder is at least one selected from thermoplastic resin, acrylic resin, sodium carboxymethyl cellulose and styrene butadiene rubber.

[0034] As a further embodiment, the positive electrode conductor is selected from carbon materials, metal materials or materials prepared by conductive in-situ curing.

[0035] As a further solution, the positive electrode current collector is a metal foil layer selected from any one of aluminum, zinc, magnesium, titanium, nickel and copper.

[0036] As a further solution, the negative electrode sheet includes a negative electrode active material, a negative electrode binder, a negative electrode conductive agent, and a negative electrode current collector.

[0037] As a further embodiment, the negative electrode active material has a coating on its surface, or may be mixed with another compound having a coating.

[0038] As a further embodiment, the coating is at least one of an oxide of the coating element, a hydroxide of the coating element, a hydroxyl oxide of the coating element, a carbonate or nitrate or phosphate or borate of the coating element, and a hydroxycarbonate of the coating element.

[0039] As a further embodiment, the coating element compound is an amorphous body or a crystalline body.

[0040] As a further solution, the separator is provided with at least one porous layer on its surface.

[0041] As yet a further aspect, the porous layer includes inorganic particles and a porous layer binder.

[0042] As a further solution, the thickness of the diaphragm layer is selected from 12 μm to 20 μm.

[0043] As a further solution, a highly safe semi-solid secondary battery is prepared by the following method:

[0044] The battery is prepared by conventional methods. After the battery is formed, the curable electrolyte is injected into the battery by secondary liquid injection, and cured at 45° C. to 75° C. for 2 h to 20 h to obtain a highly safe semi-solid secondary battery.

[0045] As a further solution, the battery prepared by the conventional method contains a single injection electrolyte.

[0046] As a further solution, the primary injection electrolyte can be understood as the electrolyte conventionally used in the prior art, and the present invention does not limit the type of the primary injection electrolyte.

[0047] As a further solution, for the purpose of convenient operation, the type and content ratio of the primary injection electrolyte can be the same as those of the solvent, additive, and inorganic electrolyte salt in the curable electrolyte.

[0048] As a further solution, the mass ratio of the primary injection electrolyte to the curable electrolyte is 1:0.2 to 1:0.35.

[0049] As a further solution, the curing temperature is selected from 50° C. to 70° C., and the curing time is selected from 3 h to 15 h.

[0050] Compared with the prior art, the present invention has at least the following beneficial effects:

[0051] The high-safety semi-solid secondary battery provided by the present invention comprises a curable electrolyte. By introducing an in-situ curing material 1 having -C=C, -COO- and -Si-O groups into the curable electrolyte, cross-linking and curing of the curable electrolyte is achieved, the ion conductivity of the curable electrolyte is improved, the decomposition of the curable electrolyte and the occurrence of redox side reactions are avoided, and the problem of redox side reactions occurring under high pressure of the conventional electrolyte is solved while improving the electrochemical performance of the curable electrolyte, thereby improving the safety performance. On the basis of the in-situ curing material 1, an in-situ curing material 2 is further introduced, and the ratio between -C=C, -COO- and -Si-O groups is further optimized by utilizing the compounding effect of the in-situ curing monomers I and II, thereby constructing a stable, uniform, high anti-swelling and redox side reaction resistant curable electrolyte, thereby obtaining a high-safety semi-solid secondary battery with high safety and high ion conductivity. DETAILED DESCRIPTION

[0052] For ease of understanding, the present invention will be described in more detail below and examples of the present invention are given, but the scope of the present invention is not limited thereby.

[0053] The present invention provides an in-situ curing additive, a curable electrolyte and a highly safe semi-solid secondary battery, comprising a semi-solid electrolyte constructed by in-situ curing monomers dispersed in the curable electrolyte, wherein the in-situ curing monomers include in-situ curing monomers I and in-situ curing monomers II, wherein the in-situ curing monomer I has a structural formula of:

[0054]

[0055] Wherein, R1-R3 are selected from C1-C4 alkyl, alkoxy, haloalkyl or haloalkoxy, R4 is selected from C1-C6 alkylene or haloalkyl, and R5 is selected from C1-C2 alkyl or haloalkyl;

[0056] The structural formula of the in-situ curing monomer II is

[0057]

[0058] Wherein, R6 is selected from C1-C4 alkylene or halogenated hydrocarbon.

[0059] In the curable electrolyte of the high-safety semi-solid secondary battery, by introducing adjacent -C=C and -COO- groups into the in-situ curing monomer I and the in-situ curing monomer II, the cross-linking and curing of the curable electrolyte is achieved, and the ion conductivity of the high-safety semi-solid secondary battery is improved, the internal impedance of the battery is effectively reduced, and the decomposition and side reactions of the curable electrolyte are alleviated. At the same time, the adjacent -C=C and -COO- optimize the cross-linking structure and active sites, so that the electrochemical capacity of the high-safety semi-solid secondary battery is further improved; on this basis, two different monomer structure cross-linking coordinations are designed, and -Si-O is further introduced into the in-situ curing monomer I, which helps to further improve the ion conductivity of the high-safety semi-solid secondary battery, and on this basis, the HF content is reduced, and the stability and flexibility of the curable electrolyte after cross-linking and curing are improved; and for the in-situ curing monomer II, the terminal olefin group is further introduced on the basis of the adjacent -C=C and -COO-, which helps to further improve the cross-linking effect and stability. In addition, the in-situ curing monomer II further introduces the terminal cyanide group on this basis, from The stability and anti-oxidation and reduction ability of the high-safety semi-solid secondary battery are improved; the highlight of the present invention is that an in-situ curing monomer I having -Si-O and adjacent groups -C=C, -COO- is proposed. The in-situ curing monomer I having -C=C, -Si-O and -COO- groups at the same time can not only optimize the cross-linking site to the greatest extent and improve the compounding effect of the three, but also avoid the possibility of side reactions between different substances when the functional groups are located on different substances, thereby further improving the safety performance of the high-safety semi-solid secondary battery; secondly, on the basis of the curing monomer I, an in-situ curing monomer II having terminal olefin groups, terminal cyano groups and adjacent groups -C=C, -COO- is further introduced, which not only improves the reaction activity by utilizing the compounding of the two, but also constructs a stable, uniform, and highly anti-expansion three-dimensional structure; and introduces a cyano group to improve stability and anti-oxidation and reduction resistance; finally, the combination of in-situ curing monomers I and II is also helpful to further optimize the ratio between -C=C, -Si-O and -COO- groups, thereby further improving the battery ion conductivity.

[0060] According to the highly safe semi-solid secondary battery containing a curable electrolyte, the present invention further proposes a curable electrolyte, comprising an in-situ curing monomer I and an in-situ curing monomer II for in-situ construction of a semi-solid electrolyte.

[0061] Based on the curable electrolyte, we also propose an in-situ curing additive, including an in-situ curing monomer I and an in-situ curing monomer II.

[0062] As some exemplary preferred schemes, in the structural formula of the in-situ curing monomer I, the number of alkoxy groups in R1-R3 is less than 3, R1-R3 are selected from C1-C2 alkyl, alkoxy, haloalkyl or haloalkoxy, R4 is selected from C1-C3 alkylene or halogenated hydrocarbon, R5 is selected from C1-C2 alkyl or haloalkyl, and in the structural formula of the in-situ curing monomer II, R6 is selected from C1-C2 alkylene or halogenated hydrocarbon.

[0063] As a further solution, the present invention also provides an in-situ curing monomer I selected from One of the in-situ curing monomers II is selected from allyl-2-cyanoacrylate.

[0064] As a further solution, the ratio of the in-situ curing monomer I to the in-situ curing monomer II is selected from a range of 2:1 to 20:1; when the ratio of the in-situ curing monomer I to the in-situ curing monomer II is greater than 20:1, the excessive in-situ curing monomer I will not be able to construct a uniform and sufficient three-dimensional framework, which not only leads to the deterioration of the battery's ability to suppress expansion, but also increases the complexity of the lithium ion conduction path, thereby affecting the battery rate performance. On the other hand, too low a content of the original curing monomer II may make it difficult for the terminal cyanide group to suppress the occurrence of redox side reactions, making the internal reaction of the battery tend to be complicated and the explosion pressure higher; and when the ratio of the in-situ curing monomer I to the in-situ curing monomer II is lower than 2:1, the impedance of the high-safety semi-solid secondary battery increases, and the ion conductivity performance decreases, which cannot meet the expected needs.

[0065] As a further solution, the ratio of the in-situ curing monomer I to the in-situ curing monomer II is selected from 4:1 to 10:1. When the ratio of the two is selected from 4:1 to 10:1, while constructing a stable, uniform, and appropriately cross-linked three-dimensional framework, the ion conductivity of the highly safe semi-solid secondary battery can be further optimized. On the one hand, the uniformly cross-linked and appropriately cross-linked three-dimensional framework helps to improve the battery's ability to suppress expansion and increase the number of cycles, while the moderately cross-linked three-dimensional framework can optimize the ion transmission path to further optimize the battery's ion conductivity. At the same time, the in-situ curing monomer I and the in-situ curing monomer II in a ratio of 4:1 to 10:1 can better exert the compounding effect of the two and cooperate with each other to obtain a highly safe semi-solid secondary battery with both excellent electrochemical performance and safety performance;

[0066] As a further solution, the mass content of the in-situ curing additive in the curable electrolyte is 0.2% to 7.5%; when the mass content of the in-situ curing additive is higher than 7.5%, too high a content of the in-situ curing additive may lead to excessive cross-linking of the three-dimensional framework, affecting the ion transmission path, thereby causing a decrease in rate performance; and when the mass content of the in-situ curing additive is lower than 0.2%, too low an in-situ curing additive may not be able to successfully construct a three-dimensional framework, making it difficult for the added in-situ curing additive to play the function of inhibiting battery expansion. At the same time, too low an in-situ curing additive may also affect the ion conductivity and the ability to inhibit redox reactions. Therefore, the mass content of the in-situ curing additive in the curable electrolyte should be maintained at 0.2% to 7.5%.

[0067] As a further solution, the content of the in-situ curing additive in the mass of the curable electrolyte is 0.5% to 5%. When the mass content of the in-situ curing additive is 0.2% to 7.5%, as the mass content of the in-situ curing additive increases, the three-dimensional framework constructed by the in-situ curing monomer becomes more uniform and stable, and the ability of the battery to inhibit expansion gradually improves. When the content reaches 0.5% to 5%, the constructed high-safety semi-solid secondary battery has a more suitable three-dimensional framework structure and higher ion conductivity. When the mass content of the in-situ curing additive is lower than 0.5%, the constructed three-dimensional framework may not be sufficient, and when the mass content of the in-situ curing additive is higher than 5%, there is a risk that the three-dimensional framework is not uniform enough. Therefore, it is preferred that the content of the in-situ curing additive in the mass of the curable electrolyte is 0.5% to 5%.

[0068] As a further solution, the curable electrolyte further includes a solvent, an additive, an inorganic electrolyte salt and an initiator.

[0069] As a further embodiment, the solvent is selected from one or more of carbonate compounds, carboxylate compounds, fluorinated compounds, ethers and epoxy compounds.

[0070] As a further embodiment, the carbonate compound is selected from any one or more of cyclic carbonate compounds and chain carbonate compounds.

[0071] As a further embodiment, the cyclic carbonate compound is selected from any one or more of ethyl carbonate, ethylene carbonate, propylene carbonate, methyl vinyl carbonate, fluoroethylene carbonate, vinyl chloride carbonate, vinylene carbonate, vinyl ethylene carbonate, methylene vinyl carbonate, fluoroethylene carbonate, trifluoromethyl vinyl carbonate, and difluoroethylene carbonate.

[0072] As a further embodiment, the chain carbonate compound is selected from any one or more of dimethyl carbonate, diethyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, dipropyl carbonate, and ethyl methyl carbonate.

[0073] As a further embodiment, the carboxylate compound is selected from any one or more of ethyl propionate, propyl propionate, ethyl butyrate, propyl acetate, butyl acetate, methyl acetate and ethyl acetate.

[0074] As a further embodiment, the fluorinated compound is selected from any one or more of fluorinated carboxylic acid ester compounds, fluorinated ether compounds and fluorinated aromatic hydrocarbon compounds.

[0075] As a further embodiment, the fluorinated carboxylic acid ester compound is selected from any one or more of ethyl difluoroacetate, difluoroethyl acetate, ethyl trifluoroacetate, ethyl trifluoropropionate, methyl trifluoropropionate, ethyl tetrafluoroacetate, methyl trifluoroacetate, and ethyl difluoropropionate.

[0076] As a further embodiment, the fluorinated ether compound is selected from any one or more of fluoroether, methyl (2,2,2-trifluoroethoxy) ethyl ether, trifluoroethyl (2,2,2-trifluoroethoxy) ethyl ether, trifluoromethyl (2,2,2-trifluoroethoxy) ethyl ether, fluorobis (trifluoromethyl) oxyethane, 2-(2,2,2-trifluoroethoxy)-1,1,1-trifluoroethane, fluorotriethyl ether, perfluoro-2-butoxyethanol, and pentafluoro-1-propyl ethyl ether.

[0077] As a further embodiment, the fluorinated aromatic compound is selected from any one or more of fluorobenzene, difluorobenzene, trifluorobenzene, perfluoromethylbenzene, tetrafluorobenzene, pentafluorobenzene, perfluorobenzene, fluorotoluene and fluoroterphenyl.

[0078] As a further embodiment, the ether compound is selected from any one or more of 1,2-dimethoxyethane, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetrahydrofuran, 1,3-dioxolane, dimethoxymethane, 1,2-dimethoxypropane, diethoxymethane, polyoxyethylene dimethyl ether, methoxypropoxypropane, and ethylene glycol dimethyl ether.

[0079] As a further embodiment, the epoxy compound is selected from any one or more of ethylene oxide, propylene oxide, butylene oxide, cyclohexene oxide, benzene oxide, 1,2-epoxyheptane, 1,2-epoxyoctane, 1,3-dioxolane, 1,3-dioxane, and 1,4-dioxane.

[0080] As a further solution, in the curable electrolyte of the present invention, the additive is selected from at least one of lithium salt compounds, nitrile compounds, organosilicon compounds, sultone compounds, and sulfate compounds.

[0081] As a further embodiment, the lithium salt compound is selected from at least one of lithium difluorophosphate, lithium difluorooxalatoborate, lithium bisoxalatoborate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium nitrate, lithium hexafluorophosphate, lithium difluorosulfonyl imide, lithium bis(trifluoromethanesulfonyl)imide, lithium fluoride, and lithium chloride.

[0082] As a further embodiment, the nitrile compound is at least one selected from the group consisting of adiponitrile, succinonitrile, hexanetrinitrile, propionitrile, benzonitrile, acetonitrile and isobutyronitrile.

[0083] As a further embodiment, the organosilicon compound is at least one selected from tris(trimethylsilyl)phosphate, tris(trimethylsilyl)phosphite, tris(trimethylsilyl)borate, polydimethylsiloxane, and trimethylchlorosilane.

[0084] As a further embodiment, the sultone compound is selected from at least one of 1,3-propane sultone, 1,3-propylene sultone, benzene sultone, cyclohexene sultone, cyclopentene sultone, vinyl sultone, octyl sultone and phenyl sultone.

[0085] As a further embodiment, the sulfate ester compound is selected from at least one of vinyl sulfate, dimethyl sulfate, ethyl sulfate, propylene sulfate, dimethoxyethane sulfate, and methoxysulfate.

[0086] As a further solution, in the curable electrolyte of the present invention, the inorganic electrolyte salt is selected from at least one of borates, phosphates, sulfates, nitrates, antimonates, arsenates, and chlorates.

[0087] As a further embodiment, the inorganic electrolyte salt is substituted with fluorine.

[0088] As a further embodiment, the inorganic electrolyte salt is selected from LiPF6 and NaPF6.

[0089] As a further embodiment, the initiator is selected from one or more of ammonium persulfate, sodium persulfate, potassium persulfate, hydrogen peroxide, tert-butyl peroxide, dibenzoyl peroxide, and azobisisobutyronitrile.

[0090] The high-safety semi-solid secondary battery further includes a positive electrode sheet, a negative electrode sheet and a separator.

[0091] As a further solution, the positive electrode sheet includes a positive electrode active material, a positive electrode binder, a positive electrode conductor, and a positive electrode current collector.

[0092] As a further solution, the positive electrode active material is selected from at least one of transition metal composite oxides and transition metal phosphate compounds.

[0093] As a further solution, the chemical general formula of the transition metal composite oxide is selected from (A) x M1 1-p B1 p O2, r(A)2Mn 1-q B2 q O3·(1 - r)AM2 1-s B3 s B3O2, (A) y (M3 2-h B4 h )2O4, any one of them, 0.05 ≤ x, 0 ≤ p ≤ 0.4, 0 ≤ q ≤ 0.4, 0 ≤ s ≤ 0.4, 0 ≤ r ≤ 1, y ≤ 1.2, 0 ≤ h ≤ 0.8, where A is an active metal ion that can be deintercalated / inserted, specifically including any one or several of Li+, Na+, K+, Mg2+, Ca 2 +, M1, M2 、 M3 is one or more transition metal elements, specifically including scandium (Sc), yttrium (Y), lanthanide elements (from lanthanum (La) to lutetium (Lu)), titanium (Ti), zirconium (Zr), hafnium (Hf), vanadium (V), niobium (Nb), tantalum (Ta), chromium (Cr), molybdenum (Mo), tungsten (W), manganese (Mn), technetium (Tc), rhenium (Re), iron (Fe), ruthenium (Ru), osmium (Os), cobalt (Co), rhodium (Rh), iridium (Ir), nickel (Ni), palladium (Pd), platinum (Pt), copper (Cu), silver (Ag), gold (Au), zinc (Zn), cadmium (Cd), mercury (Hg), one or more of them, and B1, B2, B3, B4 are doping elements, specifically including one or more of aluminum (Al), cobalt (Co), magnesium (Mg), tantalum (Ta), tungsten (W), niobium (Nb), zirconium (Zr), calcium (Ca), vanadium (V), molybdenum (Mo), chromium (Cr), lanthanum (La), scandium (Sc), lutetium (Lu), yttrium (Y), and boron (B).

[0094] As a further solution, the chemical general formula of the transition metal phosphate compound is (C) z (M4 1-v B5 v )PO4, 0 < z ≤ 1, 0 ≤ v ≤ 0.4, C represents an active metal ion that can be deintercalated / inserted, specifically including Li+, Na+, K+, Mg2+, Ca 2+ any one or more, M4 represents one or more transition metal elements, specifically including scandium (Sc), yttrium (Y), lanthanide elements (from lanthanum (La) to lutetium (Lu)), titanium (Ti), zirconium (Zr), hafnium (Hf), vanadium (V), niobium (Nb), tantalum (Ta), chromium (Cr), molybdenum (Mo), tungsten (W), manganese (Mn), technetium (Tc), rhenium (Re), iron (Fe), ruthenium (Ru), osmium (Os), cobalt (Co), rhodium (Rh), iridium (Ir), nickel (N i), palladium (Pd), platinum (Pt), copper (Cu), silver (Ag), gold (Au), zinc (Zn), cadmium (Cd), mercury (Hg) or one or more thereof; B5 is a doping element, specifically including one or more of aluminum (Al), cobalt (Co), magnesium (Mg), tantalum (Ta), tungsten (W), niobium (Nb), zirconium (Zr), calcium (Ca), vanadium (V), molybdenum (Mo), chromium (Cr), lanthanum (La), scandium (Sc), lutetium (Lu), yttrium (Y) and boron (B).

[0095] As a further embodiment, the positive electrode binder is at least one selected from thermoplastic resin, acrylic resin, sodium carboxymethyl cellulose and styrene butadiene rubber.

[0096] As a further embodiment, the thermoplastic resin includes at least one of polyvinylidene fluoride, polyvinylidene fluoride, copolymers of vinylidene fluoride, polytetrafluoroethylene, copolymers of vinylidene fluoride-hexafluoropropylene, copolymers of tetrafluoroethylene-hexafluoropropylene, copolymers of tetrafluoroethylene-perfluoroalkyl vinyl ether, copolymers of ethylene-tetrafluoroethylene, copolymers of vinylidene fluoride-tetrafluoroethylene, copolymers of vinylidene fluoride-trifluoroethylene, copolymers of vinylidene fluoride-trichloroethylene, copolymers of vinylidene fluoride-fluoroethylene, copolymers of vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene, thermoplastic polyimide, polyethylene and polypropylene.

[0097] As a further embodiment, the acrylic resin includes at least one of vinyl acrylate resin, methyl acrylate resin, butyl acrylate resin, acrylic styrene resin, acrylate resin, acrylate copolymer resin, acrylic resin, and acrylic emulsion resin.

[0098] As a further embodiment, the positive electrode conductor is selected from carbon materials, metal materials or materials prepared by conductive in-situ curing.

[0099] As a further solution, the carbon material is selected from any one of carbon nanotubes, graphite, graphene, carbon fiber, activated carbon, and Super P.

[0100] As a further solution, the metal material is selected from a single substance or oxide of any one element selected from silver, copper, nickel, cobalt, aluminum, titanium, rhodium and gold.

[0101] As a further solution, the positive electrode current collector is a metal foil layer selected from any one of aluminum, zinc, magnesium, titanium, nickel and copper.

[0102] As a further solution, the negative electrode sheet includes a negative electrode active material, a negative electrode binder, a negative electrode conductive agent, and a negative electrode current collector.

[0103] As a further embodiment, the negative electrode active material is selected from at least one of natural graphite, artificial graphite, intermediate phase microcarbon beads, hard carbon, soft carbon, silicon (oxygen), silicon (oxygen)-carbon composites, alloy compounds, Sn, SnO, and SnO2.

[0104] As a further embodiment, the negative electrode active material has a coating on its surface, or may be mixed with another compound having a coating.

[0105] As a further embodiment, the coating is at least one of an oxide of the coating element, a hydroxide of the coating element, a hydroxyl oxide of the coating element, a carbonate or nitrate or phosphate or borate of the coating element, and a hydroxycarbonate of the coating element.

[0106] As a further embodiment, the coating element compound is an amorphous body or a crystalline body.

[0107] In a further embodiment, the coating element is any one or more of magnesium (Mg), aluminum (Al), cobalt (Co), K, Na, calcium (Ca), silicon (Si), titanium (Ti), vanadium (V), tin (Sn), germanium (Ge), gallium (Ga), boron (B), arsenic (As), zirconium (Zr), tantalum (Ta), niobium (Nb), and lanthanum (La).

[0108] As a further solution, the type of the negative electrode binder is not limited, and technicians can choose according to actual needs, including at least one of styrene-butadiene rubber, styrene-butadiene rubber, water-based acrylic resin, carboxymethyl cellulose, sodium carboxymethyl cellulose, and polyacrylate.

[0109] As a further solution, the type of the negative electrode conductive agent is not limited, and technicians can choose according to actual needs, including at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, multi-arm carbon nanotubes, single-walled carbon nanotubes, graphene, conductive carbon black and carbon nanofibers.

[0110] As a further solution, the negative electrode current collector is selected from a metal material that can conduct ions, including any metal foil layer of copper, aluminum, nickel, and tin.

[0111] As a further solution, the isolation film is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate, polyimide and aramid.

[0112] As a further solution, the separator is provided with at least one porous layer on its surface.

[0113] As yet a further aspect, the porous layer includes inorganic particles and a porous layer binder.

[0114] As a further embodiment, the inorganic particles are selected from at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide and barium sulfate.

[0115] As a further embodiment, the porous layer is selected from at least one of polyvinylidene fluoride-hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, carboxymethyl cellulose sodium, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene and polyhexafluoropropylene.

[0116] As a further solution, the thickness of the diaphragm layer is selected from 12 μm to 20 μm.

[0117] As a further solution, a highly safe semi-solid secondary battery is prepared by the following method:

[0118] The battery is prepared by conventional methods. After the battery is formed, the curable electrolyte is injected into the battery by secondary liquid injection, and cured at 45° C. to 75° C. for 2 h to 20 h to obtain a highly safe semi-solid secondary battery.

[0119] Adding curable electrolyte by secondary injection avoids the impact of subsequent operations after the first injection on the curable electrolyte, and also makes it possible to accurately control the time and temperature during the polymerization and curing process. This precise control helps ensure that the curable electrolyte is cured under ideal conditions, improves the consistency and repeatability of battery performance, and provides technical support for the development of more reliable and safe battery systems.

[0120] As a further solution, the battery prepared by the conventional method contains a single injection electrolyte.

[0121] As a further solution, the single-injection electrolyte can be understood as the electrolyte conventionally used in the prior art. The present invention does not limit the type of the single-injection electrolyte, which generally includes solvents, additives and inorganic electrolyte salts. The types and content ratios of the solvents, additives and inorganic electrolyte salts are selected within the general range of the field. For example, the same or different composition schemes can be independently selected within the types and content ratios of the solvents, additives and inorganic electrolyte salts in the above-mentioned curable electrolyte.

[0122] As a further solution, for the purpose of convenient operation, the type and content ratio of the primary injection electrolyte can be the same as those of the solvent, additive, and inorganic electrolyte salt in the curable electrolyte.

[0123] As a further solution, the mass ratio of the primary injection electrolyte to the curable electrolyte is 1:0.2 to 1:0.35.

[0124] As a further solution, the curing temperature is selected from 50°C to 70°C, and the curing time is selected from 3h to 15h. A higher curing temperature may optimize the in-situ curing effect and obtain a more stable and safe semi-solid secondary battery, but too high a temperature may lead to an increase in the degree of cross-linking of the in-situ cured monomers, thereby resulting in a decrease in rate performance. Although extending the curing time can increase the degree of cross-linking of the in-situ cured monomers, thereby improving the capacity retention rate and battery safety, it may also lead to excessive cross-linking resulting in a decrease in rate performance. Therefore, the curing time is preferably 3h to 15h.

[0125] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0126] The chemical raw materials involved in the following examples and comparative examples are all prior art and are commercially available. The experimental devices, test devices, etc. involved in the following examples and comparative examples are all conventional devices in the art, without special requirements and limitations.

[0127] Example 1

[0128] 1. Preparation of lithium-ion high-safety semi-solid secondary batteries

[0129] The positive electrode active material lithium cobalt oxide, the conductive agent Super P, polyvinylidene fluoride, and carbon nanotubes were mixed in a weight ratio of 95:2:2.5:0.5, N-methylpyrrolidone was added, and the mixture was stirred evenly under the action of a vacuum mixer to obtain a positive electrode slurry, wherein the solid content of the positive electrode slurry was 70wt%. The obtained positive electrode slurry was evenly coated on the positive electrode current collector aluminum foil, and the aluminum foil coated with the positive electrode slurry was dried at 90°C, and then cold pressed, cut, and slit to obtain a positive electrode sheet.

[0130] The negative electrode active materials graphite, silicon (oxygen), carboxymethyl cellulose, binder styrene butadiene rubber, polyacrylate, multi-arm carbon nanotubes, and single-wall carbon nanotubes are mixed in a weight ratio of 85.5:10:0.6:1.3:2:0.5:0.1, deionized water is added, and the negative electrode slurry is obtained under the action of a vacuum mixer. The negative electrode slurry is evenly coated on the negative electrode current collector copper foil; the copper foil is dried at 80°C, and then cold pressed, cut, and slit to obtain the negative electrode sheet.

[0131] In a dry argon atmosphere glove box, EC / EMC (1:9, wt.) solvent, 0.5% vinyl sulfate, and 8% fluoroethylene carbonate were dissolved and stirred thoroughly, and then 1.1M LiPF6 was added and mixed evenly to obtain a primary injection electrolyte. 20% of the electrolyte was mixed evenly with polymer monomers and ammonium persulfate to obtain a curable electrolyte (polymer monomers, addition amounts and types are shown in Table 1).

[0132] The isolation film is a 16μm thick polyethylene isolation film.

[0133] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play a role of isolation. After welding the pole ears, they are placed in the outer packaging foil aluminum-plastic film, dried, and injected with a primary injection electrolyte. After vacuum packaging, standing, and formation, a curable electrolyte is added. After sufficient standing, it is heated and polymerized (the heating temperature and polymerization time are shown in Table 1), and a safe semi-solid battery is obtained after a capacity test.

[0134] Example 2-15

[0135] Some parameters in Example 1 were changed, and the remaining parameters were prepared in the same manner as in Example 1. The parameter changes are shown in Table 1.

[0136] Example 16

[0137] Preparation of sodium ion batteries

[0138] Will Na 0.44MnO2, conductive agent Super P, polyvinylidene fluoride, and carbon nanotubes are mixed in a weight ratio of 95:2:2.5:0.5, and N-methylpyrrolidone is added to prepare a positive electrode slurry and coated on the positive electrode current collector aluminum foil. The aluminum foil coated with the positive electrode slurry is dried at 90°C, and then cold pressed, cut and slit to obtain a positive electrode sheet.

[0139] The negative electrode active material hard carbon, carboxymethyl cellulose, binder styrene butadiene rubber, polyacrylate, multi-arm carbon nanotubes, and single-wall carbon nanotubes are mixed in a weight ratio of 85.5:0.6:1.3:2:0.5:0.1, deionized water is added, and the negative electrode slurry is obtained under the action of a vacuum mixer. The negative electrode slurry is evenly coated on the negative electrode current collector copper foil; the copper foil is dried at 80°C, and then cold pressed, cut, and slit to obtain the negative electrode sheet.

[0140] In a dry argon atmosphere glove box, EC / EMC (1:9, wt.) solvent, 0.5% vinyl sulfate, and 8% fluoroethylene carbonate were dissolved and stirred thoroughly, and then 1.1M NaPF6 was added and mixed evenly to obtain a primary injection electrolyte. 20% of the electrolyte was mixed evenly with polymer monomers and ammonium persulfate to obtain a high-safety semi-solid secondary battery (polymer monomers, addition amounts and types are shown in Table 1).

[0141] The isolation film is a 16μm thick polyethylene isolation film.

[0142] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play a role of isolation. After welding the pole ears, they are placed in the outer packaging foil aluminum-plastic film, dried, and injected with a primary injection electrolyte. After vacuum packaging, standing, and formation, a curable electrolyte is added. After sufficient standing, it is heated and polymerized (the heating temperature and polymerization time are shown in Table 1), and a safe semi-solid battery is obtained after a capacity test.

[0143] Comparative Examples 1-6

[0144] Some parameters in Comparative Examples 1-6 were changed, and the rest were prepared in the same manner as in Example 1. The parameter changes are shown in Table 1.

[0145] Comparative Example 7

[0146] Some parameters of Example 16 were changed, and the rest was prepared in the same manner as Example 16. The parameter changes are shown in Table 1.

[0147] Comparative Example 8

[0148] The preparation is carried out in the same manner as in Example 1, except that the curable electrolyte is injected at the same time as the primary injection electrolyte.

[0149] Test method:

[0150] (1) Lithium / sodium ion battery cycle performance test

[0151] Place the lithium-ion battery in a 25°C thermostat and let it stand for 2 hours to allow the secondary battery to reach a constant temperature. Charge the battery that has reached a constant temperature at a constant current of 0.5C (25°C) to a voltage of 4.4V (LCO) or 3.95V (sodium layered oxide), then discharge it at a constant current of 0.5C to a voltage of 3V (LCO) or 1.5V (sodium layered oxide). This is one cycle, and the discharge capacity is recorded. Cycle capacity retention rate = discharge capacity of the nth cycle / discharge capacity of the first cycle * 100%. The discharge capacity of the first cycle is recorded as C0.

[0152] (2) Battery rate performance test

[0153] After the battery cell is fully charged, it is discharged at a 2C rate to obtain a discharge capacity C1, C1 / C0=(C1-C0) / C0*100%.

[0154] (3) Explosion pressure test

[0155] The battery was charged to 100% SOC and then placed in a sealed container. The battery was then continuously heated until it exploded due to thermal runaway, and the maximum gas pressure (KPa) generated after thermal runaway was tested.

[0156] (4) Acupuncture performance test

[0157] At 25±3℃, pierce the steel nail into the center of the fully charged cell at a speed of 150mm / s until it penetrates, and then withdraw the nail after 10 minutes. The diameter of the steel nail is 2.45mm, the length is 45mm, and the tip length range is between 2mm. If there is no fire or explosion, it passes the test.

[0158] 3. Test results

[0159] The test results of Examples 1-16 and Comparative Examples 1-8 are shown in Table 2.

[0160] Table 1

[0161]

[0162]

[0163] Note: Monomer 1 is of formula I-2, monomer 2 is of formula I-6, monomer 3 is of formula I-8, monomer 4 is of formula I-5; monomer 5 is allyl-2-cyanoacrylate.

[0164] Table 2

[0165]

[0166]

[0167] Examples 1-16 as a whole show better cycle capacity retention, battery rate and explosion pressure than Comparative Examples 1-8. By comparing Examples 1 and 16 and Comparative Examples 1 and 7, it can be seen that the addition of in-situ curing monomer I and in-situ curing monomer II can improve the electrochemical capacity and cycle stability of lithium ion high-safety semi-solid secondary batteries and sodium ion high-safety semi-solid secondary batteries and improve safety. This may be due to the introduction of -C=C, -Si-O and -COO- groups, which helps to optimize the solid electrolyte structure and improve the ion channels inside the solid electrolyte, while enhancing its stability and flexibility, and reducing the HF content, thereby effectively improving the electrochemical performance and safety performance of the high-safety semi-solid secondary battery.

[0168] In addition, from Example 2, Comparative Examples 2 and 3, it can be observed that the electrochemical performance and safety stability of Example 2 in which -C=C, -Si-O and -COO- functional groups are simultaneously present are higher than those of Comparative Examples 2 and 3 in which -C=C, -Si-O and -COO- are not simultaneously present. This may be because the compounding effect of -C=C, -Si-O and -COO- helps to improve the performance of high-safety semi-solid secondary batteries; for Example 2, it can be observed from the comparison of Comparative Example 4 that even if the in-situ cured monomer contains -C=C, -Si-O and -COO-, when the three functional groups are respectively located on different in-situ cured products, their electrochemical performance and safety stability are still lower than those located on the same compound. This may be because the adjacent -C=C and -COO- improve the ion conductivity while optimizing the cross-linking structure and active sites. On this basis, -C=C, -Si-O and -COO- are located in the same in-situ cured product, avoiding the occurrence of battery side reactions between multiple in-situ cured products, thereby improving battery stability.

[0169] From the comparison between Example 2, Comparative Examples 5 and 6, it can be seen that the compounding effect between the in-situ curing monomer I and the in-situ curing monomer II is very important. When only the in-situ curing monomer I is present (Comparative Example 5), compared with the Comparative Example I without adding the in-situ curing monomer, the electrochemical performance is improved to a certain extent, but the explosion pressure is not optimized much. This may be because when only the in-situ curing monomer I is present, the three-dimensional network structure is not fully formed, resulting in poor cycle stability and reduced safety performance; when only the in-situ curing monomer II is added (Comparative Example 6), the in-situ curing monomer I is lacking in doping. Although the pressure of Comparative Example 5 is optimized to a certain extent during the explosion, the electrochemical performance is significantly reduced. Therefore, the compounding between the in-situ curing monomer I and the in-situ curing monomer II is very important. The compounding of the two helps to optimize the network structure while improving the electrochemical performance of the battery, improve the electrochemical stability and antioxidant reduction ability, and form a battery with high cycle, rate and safety performance.

[0170] Example 2 and Comparative Example 8 compare the effects of the single injection method and the double injection method on the performance of high-safety semi-solid secondary batteries. It can be observed from Comparative Example 8 that when the single injection method is used, the capacity retention rate and the battery rate after 200 cycles at room temperature are significantly lower than those of Example 2, and the explosion pressure is also higher than that of Example 2. This may be because the subsequent operations after the single injection affect the curing of the curable electrolyte. Therefore, Example 2 exhibits better performance than Comparative Example 8.

[0171] By comparing Example 2 with Example 13, it can be seen that within the structural formula range of in-situ curing monomer I and in-situ curing monomer II, as the content of the siloxane group increases, Example 13 exhibits better rate performance, indicating that the siloxane group has a positive effect on improving the rate performance, and further comparing Example 13 with Example 14, it is found that by shortening the carbon chain length in the silane, the rate performance of Example 14 is further increased, and the explosion pressure is optimized, indicating that the short carbon chain silane group is beneficial to improving the rate performance and safety of the battery. In addition, by comparing Example 2 with Example 15, it can be seen that reducing the number of carbon atoms between the siloxane group and the carboxylate group will optimize the rate performance and explosion pressure.

[0172] From the comparison of Examples 2, 8, and 9, it can be seen that the ratio of in-situ curing monomer I to in-situ curing monomer II is also an important factor affecting the cycle stability and safety of high-safety semi-solid secondary batteries. When the ratio ranges from 4:1 to 10:1, it helps to obtain batteries with uniform and stable structure, high electrochemical capacity, and good cycle performance while ensuring the improvement of safety performance. Therefore, according to Examples 2, 8, and 9, the ratio of in-situ curing monomer I to in-situ curing monomer II is preferably 4:1 to 10:1.

[0173] The total content of in-situ curing monomer I and in-situ curing monomer II in the curable electrolyte is also one of the factors affecting the comprehensive performance of high-safety semi-solid secondary batteries. From the comparison of Examples 2 and 10-12, it can be observed that with the gradual increase of the total content of in-situ curing monomers, the explosion pressure gradually decreases. This may be because a higher content of in-situ curing monomers helps to form a more stable solid electrolyte, but it may also cause a slight decrease in rate performance. Therefore, according to Examples 2 and 10-12, it is preferred that the total content of in-situ curing monomer I and in-situ curing monomer II in the curable electrolyte is 0.5% to 5%, so as to obtain a high-safety semi-solid secondary battery with an excellent balance of safety and electrochemical performance.

[0174] For in-situ curing monomers, curing time and temperature both affect their curing degree. From the comparison of Examples 1-3, it can be seen that with the gradual increase of curing temperature, the explosion pressure is gradually optimized, but the rate performance is affected by the in-situ curing monomers that are too tightly cross-linked. Therefore, compared with Examples 1 and 3, Example 2 exhibits more balanced electrochemical capability and safety; and from the comparison of Examples 2 and 4-7, it can be seen that with the extension of curing time, the capacity retention rate after 200 cycles of normal temperature cycling gradually increases, and the explosion pressure gradually decreases, indicating that with the extension of curing time, the curing degree gradually increases, but excessive cross-linking may affect the battery rate performance. Therefore, according to Examples 1-6, the preferred curing temperature is 50°C to 70°C, and the curing time is 3h to 15h.

[0175] The technical features of the above-described embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above-described embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. Although the embodiments of the present invention have been shown and described above, it can be understood that the above-described embodiments are exemplary and cannot be understood as limitations of the present invention. Those of ordinary skill in the art can change, modify, replace and deform the above-described embodiments within the scope of the present invention. In addition, those of ordinary skill in the art can combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples without contradiction.

Claims

1. An in-situ curing additive, characterized in that: It comprises an in-situ curing monomer I and an in-situ curing monomer II, wherein the structural formula of the in-situ curing monomer I is: Wherein, R1-R3 are selected from C1-C4 alkyl, alkoxy, haloalkyl or haloalkoxy, R4 is selected from C1-C6 alkylene or haloalkyl, and R5 is selected from C1-C2 alkyl or haloalkyl; The structural formula of the in-situ curing monomer II is Wherein, R6 is selected from C1-C4 alkylene or halogenated hydrocarbon.

2. The in-situ curing additive according to claim 1, characterized in that: In the structural formula of the in-situ curing monomer I, the number of alkoxy groups in R1-R3 is less than 3, R1-R3 is selected from C1-C2 alkyl, alkoxy, halogenated alkyl or halogenated alkoxy, R4 is selected from C1-C3 alkylene or halogenated hydrocarbon, and R5 is selected from C1-C2 alkyl or halogenated alkyl; In the structural formula of the in-situ curing monomer II, R6 is selected from a C1-C2 alkyl group or a halogenated alkyl group.

3. The in-situ curing additive according to claim 1, characterized in that: The ratio of the in-situ curing monomer I to the in-situ curing monomer II is selected from 2:1 to 20:1; Preferably, the ratio of the in-situ curing monomer I to the in-situ curing monomer II is selected from a range of 4:1 to 10:

1.

4. A curable electrolyte, characterized in that: The invention comprises the in-situ curing additive according to claim 1 to claim 3.

5. The curable electrolyte according to claim 4, characterized in that: The mass content of the in-situ curing additive in the curable electrolyte is 0.2% to 7.5%; Preferably, the mass content of the in-situ curing additive in the curable electrolyte is 0.5% to 5%. The curable electrolyte also includes a solvent, an additive, an inorganic electrolyte salt and an initiator; The solvent is selected from one or more of carbonate compounds, carboxylate compounds, fluorinated compounds, ethers and epoxy compounds; The carbonate compound is selected from any one or more of cyclic carbonate compounds and chain carbonate compounds; In the curable electrolyte of the present invention, the additive is selected from at least one of lithium salt compounds, nitrile compounds, organosilicon compounds, sultone compounds, and sulfate compounds; In the curable electrolyte of the present invention, the inorganic electrolyte salt is selected from at least one of borates, phosphates, sulfates, nitrates, antimonates, arsenates, and chlorates; Preferably, the inorganic electrolyte salt is substituted with fluorine; The initiator is selected from one or more of ammonium persulfate, sodium persulfate, potassium persulfate, hydrogen peroxide, tert-butyl peroxide, dibenzoyl peroxide, and azobisisobutyronitrile.

6. A highly safe semi-solid secondary battery, characterized in that: An electrolyte comprising the curable electrolyte solution according to claim 4 to claim 5.

7. The highly safe semi-solid secondary battery according to claim 6, characterized in that: The high-safety semi-solid secondary battery further includes a positive electrode sheet, a negative electrode sheet and a separator.

8. The highly safe semi-solid secondary battery according to claim 6, characterized in that: The positive electrode sheet comprises a positive electrode active material, a positive electrode binder, a positive electrode conductive agent, and a positive electrode current collector; The positive electrode active material is selected from at least one of transition metal composite oxides and transition metal phosphate compounds; The transition metal composite oxide chemical formula is selected from (A) x M1 1-p B1 p O2、r(A)2Mn 1-q B2 q O3·(1-r)AM2 1- s B3 s B3O2, (A) y (M3 2-h B4 h )2O4, 0.05≤x, 0≤p≤0.4, 0≤q≤0.4, 0≤s≤0.4, 0≤r≤1, y≤1.2, 0≤h≤0.8, wherein A is an active metal ion that can be deintercalated, specifically including Li+, Na+, K+, Mg2+, Ca 2 +Any one or more of M1, M2 、 M3 is one or more transition metal elements, specifically including scandium (Sc), yttrium (Y), lanthanide elements (from lanthanum (La) to lutetium (Lu)), titanium (Ti), zirconium (Zr), hafnium (Hf), vanadium (V), niobium (Nb), tantalum (Ta), chromium (Cr), molybdenum (Mo), tungsten (W), manganese (Mn), technetium (Tc), rhenium (Re), iron (Fe), ruthenium (Ru), osmium (Os), cobalt (Co), rhodium (Rh), iridium (Ir), nickel (Ni), palladium (Pd), platinum B1, B2, B3, and B4 are doping elements, specifically including one or more of aluminum (Al), cobalt (Co), magnesium (Mg), tantalum (Ta), tungsten (W), niobium (Nb), zirconium (Zr), calcium (Ca), vanadium (V), molybdenum (Mo), chromium (Cr), lanthanum (La), scandium (Sc), lutetium (Lu), yttrium (Y), and boron (B); The chemical general formula of the transition metal phosphate compound is (C) z (M4 1-v B5 v )PO4, where 0 < z ≤ 1, 0 ≤ v ≤ 0.4, C represents an active metal ion that can be deintercalated, specifically including any one or more of Li+, Na+, K+, Mg2+, Ca 2 +, M4 represents one or more transition metal elements, specifically including one or more of scandium (Sc), yttrium (Y), lanthanide elements (from lanthanum (La) to lutetium (Lu)), titanium (Ti), zirconium (Zr), hafnium (Hf), vanadium (V), niobium (Nb), tantalum (Ta), chromium (Cr), molybdenum (Mo), tungsten (W), manganese (Mn), technetium (Tc), rhenium (Re), iron (Fe), ruthenium (Ru), osmium (Os), cobalt (Co), rhodium (Rh), iridium (Ir), nickel (Ni), palladium (Pd), platinum (Pt), copper (Cu), silver (Ag), gold (Au), zinc (Zn), cadmium (Cd), mercury (Hg); B5 is a doping element, specifically including one or more of aluminum (Al), cobalt (Co), magnesium (Mg), tantalum (Ta), tungsten (W), niobium (Nb), zirconium (Zr), calcium (Ca), vanadium (V), molybdenum (Mo), chromium (Cr), lanthanum (La), scandium (Sc), lutetium (Lu), yttrium (Y), and boron (B); The positive electrode binder is selected from at least one of thermoplastic resin, acrylic resin, sodium carboxymethyl cellulose and styrene butadiene rubber; The positive electrode conductive agent is selected from carbon materials, metal materials or materials prepared by conductive in-situ curing; The positive electrode current collector is a metal foil layer selected from any one of aluminum, zinc, magnesium, titanium, nickel and copper.

9. The highly safe semi-solid secondary battery according to claim 6, characterized in that: The negative electrode sheet comprises a negative electrode active material, a negative electrode binder, a negative electrode conductive agent, and a negative electrode current collector; The negative electrode active material has a coating on its surface, or may be mixed with another compound having a coating; Preferably, the coating is at least one of an oxide of a coating element, a hydroxide of a coating element, an oxyhydroxide of a coating element, a carbonate or a nitrate or a phosphate or a borate of a coating element, and a hydroxycarbonate of a coating element; Preferably, the coating element compound is an amorphous body or a crystalline body; The isolation membrane is provided with at least one surface porous layer; Preferably, the porous layer comprises inorganic particles and a porous layer binder; The high-safety semi-solid secondary battery further includes a separator layer; The thickness of the diaphragm layer is selected from 12 μm to 20 μm.

10. The highly safe semi-solid secondary battery according to claim 6, characterized in that: The highly safe semi-solid secondary battery is prepared by the following method: The battery is prepared by a conventional method. After the battery is formed, the curable electrolyte is injected into the battery by a secondary liquid injection method, and cured at 45° C. to 75° C. for 2 h to 20 h to obtain a highly safe semi-solid secondary battery. The battery prepared by the conventional method contains a primary injection electrolyte; The primary injection electrolyte may have the same type and content ratio as the solvent, additive, and inorganic electrolyte salt in the curable electrolyte; The mass ratio of the primary injection electrolyte to the curable electrolyte is 1:0.2 to 1:0.35; The curing temperature is selected from 50° C. to 70° C., and the curing time is selected from 3 h to 15 h.

Citation Information

Patent Citations

  • Lithium ion battery composite positive electrode material, preparation method thereof and lithium ion battery

    CN113380990A

  • Preparation method of polymer powder, spray drying equipment, battery diaphragm and secondary battery

    CN115353750A

  • Additive agent for secondary battery, electrolytic solution for secondary battery that contains the same, and secondary battery including the same

    JP2017069204A

  • Disubstituted halogenated polyether and polymer electrolyte comprising the same

    JP2019157008A

  • A manufacturing process of Lithium cell usinginorganic solvent catalyst and metallic catalyst

    KR1020020043535A